2021
DOI: 10.9770/jesi.2021.9.2(30)
|View full text |Cite
|
Sign up to set email alerts
|

The effect of institutional innovations on tourism spending in developed countries

Abstract: The new institutional economy deals with the study of innovations that can be reflected in various national sectors, including tourism. The objective of the presented study was to evaluate the significance of the effects of institutional innovations on tourism spending. The analyses included data from databases of the World Travel & Tourism Council (business tourism spending (BTS), leisure tourism spending (LTS), domestic tourism spending (DTS) and visitor exports (foreign spending) (VEFS)) and the Global Inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the majority of the existing literature on destination image study, tourist satisfaction, and behavioural intention focus primarily on well-established destinations (Chi & Qu, 2008). A relatively less researched area in the tourism literature is how international tourists perceive the image of the emerging destination (Stylidis et al, 2017;Rigelsky et al, 2021). Mongolia has an important geographical location in East Asia with a vast 1.566 million sq km area with 3.2 million inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the majority of the existing literature on destination image study, tourist satisfaction, and behavioural intention focus primarily on well-established destinations (Chi & Qu, 2008). A relatively less researched area in the tourism literature is how international tourists perceive the image of the emerging destination (Stylidis et al, 2017;Rigelsky et al, 2021). Mongolia has an important geographical location in East Asia with a vast 1.566 million sq km area with 3.2 million inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a regulatory framework and policy approach is based on governmental knowledge and the political environment (Rigelsk y et al, 2021). Political (in)stability (Nadeem et al, 2020) and corruption have been found to affect innovation (Xie et al, 2019).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Currently, a small amount of literature has paid attention to the research on the relationship between the business environment and the tourism industry. Rigelský et al ( 2021 ) conducted panel regression processing using the data of 36 OECD countries in the world tourism and Tourism Council database. The research found that institutional innovation had the greatest impact on Tourism expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, a small amount of literature has paid attention to the research on the relationship between business environment and tourism industry. Rigelský et al ( 2021 ) empirically found that institutional innovation has the greatest impact on tourism expenditure by using the data of 36 OECD countries in the WTTC database. Gani and Clemes ( 2021 ) analyzed the tourism data of 24 countries within the framework of the gravity model and concluded that an open trade environment and a good business environment could attract more international business tourists and obtain additional benefits.…”
Section: Literature Reviewmentioning
confidence: 99%